FACTORS THAT AFFECT THE DEVELOPMENT OF FUNCTIONAL HEART DISORDERS IN CHILDREN WITH UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA - Abdullaeva Dilafruz Gayratovna,; Abdullaeva Diloram Telmanovna,; Mirrokhimova Maktuba Habibullayevna,; Kurbanova Dilbar Rakhimovna, (The Bioscan, 2025)
Connective tissue dysplasia is a complex and rare ontogenetic developmental anomaly that remains one of the least studied problems in modern medicine. It serves as a morphological basis for functional changes in the heart. The study examined 79 preschool and school-age children with connective tissue dysplasia and minor heart developmental anomalies. It was found that external phenotypic markers of connective tissue dysplasia syndrome and stigmas of embryogenesis occur with high frequency. Clinical manifestations of the disease were also recorded. Functional disorders of the heart associated with phenotypic features of connective tissue dysplasia and stigmas of dysembryogenesis were investigated. Additionally, the anamnestic data of mothers influencing the probability of developing connective tissue dysplasia in children were analyzed.